2017
DOI: 10.1051/bioconf/20170902024
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effect of 8 closures in controlled industrial conditions on the shelf life of a red wine

Abstract: Aims: The management of O 2 , CO 2 and SO 2 at bottling and the choice of the closure are two key factors of the shelf life of wine in bottles before bringing them to market. The impact of four screw caps, two synthetic and two technical corks was evaluated on a red wine of Merlot/Tannat. Methods and results:Analytical monitoring (O 2 , CO 2 , SO 2 , aphrometric pressure, L*, a*, b*) was carried out during 538 days of storage at 20 • C. Two sensory analyses at 10 and 17 months completed the study.The wine was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
(36 reference statements)
0
4
0
Order By: Relevance
“…A synthetic stopper not only has an adsorption capacity for volatile compounds such as some terpene rose oxides with lychee flavours in some white wines, as well as methoxypyrazines, but also can absorb organic acids in the wine in polyethylene, resulting in a loss of aroma intensity and fruit taste [ 85 ]. Other studies have shown that synthetic stoppers can be of great value for young wines and those aged for a short period [ 91 ]. It has been reported that the polyethylene (PE) film in synthetic stoppers has a good adsorption effect on chloroanisole in wine, and the concentration of chloroanisole at room temperature reaches equilibrium within three days after the wine comes into contact with the PE film.…”
Section: Factors Impacting the Flavour Of Winementioning
confidence: 99%
“…A synthetic stopper not only has an adsorption capacity for volatile compounds such as some terpene rose oxides with lychee flavours in some white wines, as well as methoxypyrazines, but also can absorb organic acids in the wine in polyethylene, resulting in a loss of aroma intensity and fruit taste [ 85 ]. Other studies have shown that synthetic stoppers can be of great value for young wines and those aged for a short period [ 91 ]. It has been reported that the polyethylene (PE) film in synthetic stoppers has a good adsorption effect on chloroanisole in wine, and the concentration of chloroanisole at room temperature reaches equilibrium within three days after the wine comes into contact with the PE film.…”
Section: Factors Impacting the Flavour Of Winementioning
confidence: 99%
“…Regarding oxygen, it comes into contact with the wine along several steps in winemaking and bottling process, hence when wine is bottled it already contains dissolved oxygen. Besides, after wine has been bottled oxygen will be present in the headspace [ 29 ]. To better control the storage and aging, oxygen in the headspace can be evaporated by vacuum and replaced by an inert gas, such as nitrogen.…”
Section: Influence Of Closurementioning
confidence: 99%
“…However, the most used and practical value is OTR [ 41 ] that may be calculated by physical measures of the stopper properties, i.e., inferring from their effective diffusion or rather indirectly by determining the oxygen concentration in the bottle or the degree of degradation of compounds in the wine or even apparent characteristics (i.e., yellow color by measuring absorbance at 420 nm or chemiluminescence) [ 34 , 42 ]. The units of OTR are usually given as mg or ml of O 2 per day, month or year [ 29 ]. This allows not only to determine the passage of oxygen, but also to easily conceive what amount may be added to the wine through bottle aging and best fits each type of wine.…”
Section: Influence Of Closurementioning
confidence: 99%
“…The relative rates of iron oxidation and reduction may explain the poor correlation noted previously between oxygen consumption and wine composition, as well as the high iron(II):iron(III) ratios (Danilewicz 2016, Danilewicz 2018, Nguyen and Waterhouse 2019) and low oxygen levels (Castellari et al 2004, del Alamo-Sanza and Nevares 2014, del Alamo-Sanza and Nevares 2018, Vidal et al 2017) commonly observed for wines in storage. Wine evidently effectively maintains reductive conditions, and only very rarely would oxygen be in constant excess (e.g.…”
Section: Iron(iii) Reduction Ratesmentioning
confidence: 94%